P160 Faecal Lactoferrin is a reliable IBD biomarker during pregnancy. (16th January 2018) - Barré, A; Tarassishin, L; Eisele, C; Hu, J; Nair, N; Stone, J; Dubinsky, M; Boone, J; Mørk, E; Thjømøe, A; Colombel, J F; Torres, J; et al.
Abstract: Background: Monitoring IBD activity during pregnancy is challenging because clinical and laboratory markers may be altered due to the physiological adaptation that occurs, and endoscopy use is limited. Fecal Lactoferrin (FL) is a non-invasive biomarker of gut inflammation used for the diagnostics and management of IBD; however, little is known about its use in pregnant women. Herein, we investigated FL concentrations in IBD and control women, participating in the MECONIUM (Exploring MEChanisms Of disease traNsmission In Utero through the Microbiome) study, prior to (T0) and during each trimester of pregnancy. Methods: 405 faecal samples [32 at T0; 50 at first trimester (T1); 134 at second trimester (T2) and 189 at third trimester (T3)] from 76 IBD women and 175 controls were analysed using a quantitative enzyme immunoassay (LACTOFERRIN SCANTM, TECHLAB®). Correlation analyses with clinical scores collected prospectively [physician global assessment (PGA), modified Harvey-Bradshaw index (HBI) for CD and partial Mayo score for UC] and with fecal calprotectin analysed using a quantitative enzyme immunoassay (CalproLabTM Calprotectin ELISA, Norway) were performed. Statistical analyses were conducting using R software. Results: The median FL (µg/ml) for pregnant was not different to that of non-pregnant women in controls (1.52 at T1 vs. 1.08 at T0; p = 0.08) and in IBD group (3.58 at T1 vs. 2.64 at T0; p = 0.53). FL was significantly higher in IBD women compared with controls at each trimester of pregnancy (Figure 1) and differed by disease activity (active vs. in remission) but showed significance at only T3 ( p = 0.002). At T3, FL significantly correlated with PGA (spearman r = 0.42; p = 0.001), partial Mayo score in UC patients (r = 0.41; p = 0.04) and with HBI in CD patients (r = 0.36; p = 0.05). Finally, FL correlated closest with fecal calprotectin (r = 0.63; p < 0.0001), especially in IBD women (r = 0.78; p < 0.0001, Figure 2) at T3. Conclusions: FL is not affected by pregnancy regardless of maternal IBD status. IBD women had higher FL levels than controls at each trimester of pregnancy. Suggesting that FL could be a reliable, non-invasive biomarker of gut inflammation to monitor IBD activity during this period.